Common eye diseases and their management - Galloway, Nicholas R. (Springer, 2006)
There have been significant advances in the diagnosis and management of eye disease since the last edition of Common Eye Diseases and their Management was published. The specialty has developed more subspecialties, and the referring doctor has to have a good knowledge of these in order to make appropriate referrals. An increased emphasis on screening has made it necessary for the primary care doctor to have a basic knowledge of eye diseases. This applies particularly to glaucoma and diabetic eye disease. The management of eye conditions in the elderly is also an important and increasing primary care problem. It has been the intention to keep explanations as simple and non-technical as possible without losing scientific accuracy and more detailed accounts should be sought in the larger textbooks. The book is essential for medical students and general practitioners as well as optometrists and nurses. It addresses problems and deals with the science of Ophthalmology at a basic level. Introducing the eye - The scope of ophthalmology - Basic anatomy and physiology of the eye - Examination of the eye - Primary eye care problems - Long sight, short sight - Common diseases of the eyelids - Common diseases of the conjunctiva and cornea - The red eye - Failing vision - Headache - Contact lenses - Problems of the eye surgeon - Cataract - Glaucoma - Retinal detachment - Squint - Tumours of the eye and adnexae - Ocular tTrauma - Problems of the medical ophthalmologist - Testing visual acuity - The inflamed eye - The ageing eye - The child’s eye - Systemic disease and the eye - Neuro-ophthalmology - Genetics and the eye - Drugs and the eye - Visual handicap - Blindness.